A new rhodamine derivative as a single optical probe for the recognition of Cu2+ and Zn2+ ions. Issue 19 (30th January 2015) - Rai, Abhishek; Kumari, Niraj; Nair, Rohini; Singh, Kiran; Mishra, Lallan
Abstract : A rhodamine-based chemosensor exhibits pink color on addition of Cu 2+ ions and is returned to colorless by addition of aqueous solution of Na2 EDTA. It fluoresces in the presence of Zn 2+ ions, displaying a color change from colorless to orange in the presence of UV light. Abstract : A bifunctional colorimetric and fluorescent chemosensor of type 3, 5-dinitro-2-hydroxy benzaldehyde rhodamine hydrazone (RHDN ) was synthesized by the condensation of 3, 5-dinitro salicylaldehyde and rhodamine B hydrazide. It was characterized using spectroscopic techniques and single crystal studies. The chemosensorRHDN exhibited remarkably enhanced absorbance and colour changes from colourless to pink color on binding with Cu 2+ ions. In contrast, Zn 2+ ions were identified by their selective binding withRHDN showing OFF–ON type fluorescence, which changes from colorless to orange color in ultra violet-light. The absorbance and emission pattern ofRHDN adduct separately with Cu 2+ and Zn 2+ ions were restored with the addition of an aqueous solution of disodium salt of ethylenediaminetetraacetic acid. Thus, RHDN was found to be very robust and reversible in its binding with Cu 2+ and Zn 2+ ions separately.